A LITERATUR REVIEW: TINGKAT LITERASI KEUANGAN PADA PENGOLAHAN KEUANGAN PRIBADI, MAHASISWA DAN UMKM - Sukma Galih Badriana; Juan Carlos, Adita; Agung Supriyadi (Jurnal Witana, 2025)
This research aims to examine the influence of financial literacy levels on financial management among students, individuals, and micro, small, and medium enterprises (MSMEs). Financial literacy is a crucial aspect of achieving financial well-being. However, many individuals, including students and MSME owners, lack the knowledge and skills to manage their finances, which can lead to financial management mistakes. Based on a literature review, this study explores how financial literacy can affect the financial behavior of students, including debt management, savings, and investments. This study uses a qualitative approach through a literature review that includes theoretical analysis and scientific literature. The results of this research are expected to provide recommendations for improving financial literacy and financial management among the community, particularly students and MSME owners, thereby enhancing their overall financial well-being. Key words: Financial literacy, financial management, students, MSMEs